Pengembangan Media Pembelajaran Multimedia Interaktif Articulate Storyline 3 dalam Menganalisis Unsur Kebahasaan Teks Negosiasi Siswa Kelas X SMK AKP Galang - Nasution, Gusti Khairani; Rita, Rita; Safina, Nila (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
This study aimed to develop and test the feasibility of interactive multimedia learning media using "Articulate Storyline 3" for analyzing linguistic elements in negotiating texts among Class X students at SMK Awal Karya Pembangunan Galang. The sample consisted of 36 students from Class X RPL-1 out of a total population of 76 students. Research and Development (R&D) approach was employed, following the ADDIE model, which included Analysis, Design, Development, Implementation, and Evaluation phases. The results indicated that the interactive multimedia learning media using "Articulate Storyline 3" was deemed suitable and valid for analyzing linguistic elements in negotiating texts by media experts (92%) and material experts (84.5%). The evaluation by teachers yielded a feasibility level of 94%, and students showed positive responses with an average of 92.5%. In conclusion, the developed learning media is valid and appropriate for instructional purposes.